Pengaruh Rendam Kaki dengan Air Hangat Campur Kencur terhadap Penurunan Tekanan Darah Lansia Hipertensi Di Desa Pohsanten - Dewi, Ni Komang Mia Sintya; Dwijayanto, I Made Rio; Kusumaningtyas, Dwi Prima Hanis (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2024)
Elderly is a phase of someone who experiences increasing age where the group is at risk of experiencing health problems. Hypertension is a condition in which a person experiences an increase in high blood pressure which reaches a systolic number of more than 140 mmHg and a diastolic number of more than 90 mmHg. Several treatments for lowering blood pressure can be carried out, one of which is with non-pharmacological actions. This study aims to determine whether or not there is an effect of soaking feet with warm water mixed with kencur on reducing blood pressure in elderly hypertensives in Pohsanten Village. This study used a quasi-experimental design with a non-equivalent control group before-after design. The population in this study were all hypertensive elderly people in Pohsanten Village. Sampling used a purposive sampling technique with 102 research samples, the experimental group totaling 51 people and the control group totaling 51 people were given the intervention of foot soaks with plain water. The analysis of this study used the Wilcoxon test and the Mann-Whitney test. In this study, the results obtained were p value = 0.000 for systolic blood pressure and diastolic blood pressure with a p value = 0.000, meaning that there was an average difference in systolic and diastolic blood pressure before and after the intervention. It can be concluded that there is an effect of soaking feet in warm water mixed with kencur on reducing blood pressure in elderly hypertensives in Pohsanten Village.